أهداف العولمة وموقف الإسلام منها - Mohammad Nashief S. Disomimba; Mohamad Yusuf Abdullah; Kalsom Ali (Akidah and Religion Studies Programme ,Faculty of Leadership and Management, USIM, 2024)
E-Proceedings Of The International Conference On Aqidah, Religions And Social Sciences (SIGMA10) “ Towards Peaceful Co-Existence And Excellence Of Ummah : An Implication Of Rahmatan Lil’Alamin” Organized by: Akidah and Religion Studies Programme, Faculty of Leadership and Management 4th November 2020